Morphological and cellular changes in aging Drosophila melanogaster midgut - Löfström, Piia (My University, 2025)
Aging is a complex biological process that impacts all living organisms. As organisms grow older, they experience a gradual decline in physiological functions, which raises the risk of developing age- associated diseases. Recent scientific advancements have uncovered several evolutionarily conserved genetic pathways and processes linked to aging. Studies regarding to the hallmarks of aging have proved the remarkable complexity and entanglement of age-related processes. However, age-related changes in intestinal morphology and cell composition, as well as the role of integrin in aging have remained largely unknown. This thesis is focused in achieving three primary aims. The aim was to study the age-related phenotypic changes in the Drosophila midgut. I analysed statistically a dataset containing data of young and aged flies, to uncover age-related regional phenotypic differences. The second aim was to study whether aging induces changes in the cellular composition in the Drosophila midgut. I have studied the effects of aging in the Drosophila midgut epithelium and lumen area, using confocal microscopy. The last aim in my thesis was to study the role of integrins in the aging Drosophila midgut. I have studied the effects of knockdown of α-integrin in Drosophila intestinal stem cells, to reveal the role of integrins in aging. Here I show that aging induces regional phenotypic changes in the Drosophila midgut. The aged phenotype demonstrated various morphological characteristics, such as relative region length changes, decreased midgut width in posterior midgut, progenitor size enlargement, proportions of progenitor cells and enteroendocrine cells increase and Delta expression increase. Furthermore, my results demonstrate a cell composition change in the midgut epithelium upon aging. The results suggest cellular detachment from basement membrane. Knockdown of α-integrin results suggested that progenitor mTORC1 signal is dependent on integrin signalling. Understanding the underlying mechanisms of aging is crucial for developing strategies to enhance healthspan and combat age-related diseases. By clarifying the complex biological processes involved in aging, researchers can identify potential targets for intervention. Such knowledge is essential for developing therapeutic approaches that can reduce the harmful effects of aging and promote healthy longevity.
Keywords: aging, midgut epithelium, intestinal cells, Drosophila melanogaster, integrin signalling, mTORC1